Governance in Blockchain Technologies & Social Contract Theories - Wessel Reijers; Fiachra O'Brolcháin; Paul Haynes (Ledger, 2016)
This paper is placed in the context of a growing number of social and political critiques of blockchain technologies. We focus on the supposed potential of blockchain technologies to transform political institutions that are central to contemporary human societies, such as money, property rights regimes, and systems of democratic governance. Our aim is to examine the way blockchain technologies canbring about - and justify - new models of governance. To do so, we draw on the philosophical works of Hobbes, Rousseau, and Rawls, analyzing blockchain governance in terms of contrasting social contract theories. We begin by comparing the justifications of blockchain governance offered by members of the blockchain developers’ community with the justifications of governance presented within social contract theories. We then examine the extent to which the model of governance offered by blockchain technologies reflects key governance themes and assumptions located within social contract theories, focusing on the notions of sovereignty, the initial situation, decentralization and distributive justice.